Tri-(Fe/F/N)-doped porous carbons as electrocatalysts for the oxygen reduction reaction in both alkaline and acidic media. Issue 36 (7th September 2020) - Diao, Yongxing; Liu, Hanmeng; Yao, Zhixia; Liu, Yaosheng; Hu, Guangxing; Zhang, Qifang; Li, Zhuang
Abstract : The uniformly dispersed Fe–N x and the increased defects after F doping make tri-(Fe/F/N)-doped porous carbons electrocatalysts have superior ORR performance than Pt/C in both alkaline and acidic media. Abstract : Developing a low cost, sustainable and high-performance precious-metal free catalyst to replace platinum (Pt)-based catalysts for the oxygen reduction reaction (ORR) in fuel cells has recently attracted significant attention. It is crucial to produce more abundant and more uniformly dispersed ORR active sites for improving the ORR performance of the catalyst. Herein, we synthesized tri-(Fe/F/N)-doped porous carbons as high-efficiency electrocatalysts for the ORR by using Fe-zeolitic imidazolate framework-8 (Fe-ZIF-8) and ammonium fluoride as precursors. The results indicate that the as-prepared FeFNC-5 catalysts exhibit superior ORR activity, methanol tolerance, and long-term stability compared to commercial 20 wt% Pt/C in both alkaline and acidic media because of the abundant and dispersed Fe–N x and pyridinic-N active sites, high specific surface area, and hierarchical porous structure. This work provides a new method and insights into the synthesis of Fe, F, and N triple-doped porous carbons as high-efficiency ORR electrocatalysts.